Company size as a moderation of ICG and ICSR on Islamic banking performance - Prastyatini, Sri Lestari Yuli; Wahidah, Umi; Jannah, Izzhatul (JPS (Jurnal Perbankan Syariah), 2025)
Purpose – This study aims to analyze the effect of Islamic corporate governance (ICG) and Islamic corporate social responsibility (ICSR) on the financial performance of Islamic banking, with company size as a moderating variable. Method – This study uses a quantitative approach using secondary data obtained from the annual reports of Islamic banks from 2014 to 2023. There are 18 Islamic commercial banks (ICB) registered from 2014 to 2023. The sampling technique uses purposive sampling, so 10 ICBs were selected as samples. The data analysis technique uses multiple linear regression and moderation regression analysis (MRA) with the help of SPSS software version 25. Findings – The results of the study show that ICG and ICSR have a positive effect on ICB financial performance. Company size can strengthen the influence of ICG and ICSR on ICB financial performance. Implications – This study can complement existing theories and provide a theoretical understanding of the factors influencing ICB financial performance. This study can help Islamic bank management improve corporate governance, accountability, and transparency to attract investors and consumers.